2018
DOI: 10.17507/jltr.0903.03
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus-based Study of Lexis in L2 English Textbooks

Abstract: Abstract-Despite the fact that textbooks are central in foreign language learning, only limited research has explored to what extent L2 textbooks support language learning and whether the content in them is relevant from a vocabulary perspective. This study investigates the vocabulary in seven English textbooks used in Swedish primary schools. A corpus has been constructed based on the words in the textbooks. By means of a concordancing software tool, the material has been analyzed by comparing the vocabulary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For example, studies of EFL textbooks (e.g. O'Loughlin, 2012; Matsuoka & Hirsh, 2010;Norberg & Nordlund, 2018;Yang & Coxhead, 2020) have shown that with utility and frequency as the primary principles of selection, the vocabulary of EFL textbooks often consists of high-frequency, standard, and formal lexical items: 'words not frequently used in common everyday language' (Norberg & Nordlund, 2018, p. 469). In contrast, stylistic variants specific to email, such as greetings, address forms, and signoffs used in email openings and closings are typically well represented (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies of EFL textbooks (e.g. O'Loughlin, 2012; Matsuoka & Hirsh, 2010;Norberg & Nordlund, 2018;Yang & Coxhead, 2020) have shown that with utility and frequency as the primary principles of selection, the vocabulary of EFL textbooks often consists of high-frequency, standard, and formal lexical items: 'words not frequently used in common everyday language' (Norberg & Nordlund, 2018, p. 469). In contrast, stylistic variants specific to email, such as greetings, address forms, and signoffs used in email openings and closings are typically well represented (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a good virtual reality environment, users' creative catalysis and knowledge construction can be deepened [16]. In the virtual space composed of VR technology, users can broaden their cognitive range, absorb the necessary knowledge based on their own cognitive abilities and feelings, and diverge and broaden their thinking [17]. The application of VR technology in education mainly aims to improve the quality of classroom teaching, strengthen students' learning motivation; and it can cultivate self-directed learning habits while changing traditional learning methods.…”
Section: Teaching Esl Vocabulary Corpus Based On Vr Technologymentioning
confidence: 99%
“…Highfrequency vocabulary deserves instructors' attention and direct teaching. Norberg and Nordlund (2018) analyzed words in textbooks in Swedish schools using corpus tools. The results show that many words in the textbooks rarely appear in common everyday language.…”
Section: Introductionmentioning
confidence: 99%